Cronius Stimpson 1860 - TAVARES, MARCOS; MENDONÇA, JOEL BRAGA DE JR. (Zenodo, 2022)
Genus Cronius Stimpson, 1860 Type species. Portunus ruber Lamarck, 1818 [Type locality: Brazil]. Remarks. Cronius currently encompass two species, the amphi-Atlantic C. ruber (Lamarck, 1818) and C. edwardsii (Lockington, 1877) (EP). This later species has been resurrected by Mantelatto et al. (2009) for specimens from the Panamanian Pacific coast. The genus had a third species, C. tumidulus , reassigned to its genus of origin, Achelous , by Mantelatto et al. (2009) (see above under Achelous tumidulus ). Cronius also includes one fossil species, C. obscurus Rathbun, 1945 (claw only) from the Miocene of Fiji (Rathbun 1945). Published as part of TAVARES, MARCOS & MENDONÇA, JOEL BRAGA DE JR., 2022, Brachyuran crabs (Crustacea, Decapoda) from the remote oceanic Archipelago Trindade and Martin Vaz, South Atlantic Ocean, pp. 1-129 in Zootaxa 5146 (1) on page 53, DOI:10.11646/zootaxa.5146.1.1, http://zenodo.org/record/7626155